2006
DOI: 10.1002/joc.1417
|View full text |Cite
|
Sign up to set email alerts
|

Relations of South American summer rainfall interannual variations with the Pacific Decadal Oscillation

Abstract: Abstract:The anomaly patterns of rainfall in South America for El Niño/Southern Oscillation (ENSO) extreme conditions stratified according to the high, low, and normal Pacific (inter-) Decadal Oscillation (PDO) phases (HPDO, LPDO and NPDO) are examined for the three bi-months of the season from November to April. El Niño (EN) and La Niña (LN) composites as well as the linear (EN − LN) and nonlinear (EN + LN) components of the precipitation anomaly patterns relative to ENSO show substantial differences among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 57 publications
9
79
0
14
Order By: Relevance
“…They found that El Niño signals in South American rainfall are more conspicuous for the warm PDO regime than for the cold PDO regime. Kayano and Andreoli (2007) suggested that the PDO creates a background for the ENSO teleconnections for the South American rainfall, acting to enhance (weaken) the rainfall anomalies when these phenomena are in the same (opposite) phase.…”
Section: Introductionmentioning
confidence: 99%
“…They found that El Niño signals in South American rainfall are more conspicuous for the warm PDO regime than for the cold PDO regime. Kayano and Andreoli (2007) suggested that the PDO creates a background for the ENSO teleconnections for the South American rainfall, acting to enhance (weaken) the rainfall anomalies when these phenomena are in the same (opposite) phase.…”
Section: Introductionmentioning
confidence: 99%
“…Ou seja, nessas décadas do século 20, quando a ODP estava na fase fria, as mínimas e máximas anuais da temperatura mínima do ar tiveram tendência de diminuição e alcançaram os valores mais baixos da série histórica (Figura 1 C e E). Como durante a fase fria da ODP, os eventos de La Niña são mais intensos e frequentes, pois a ODP e o ENOS estão em fase fria (Kayano & Andreoli, 2007), no Rio Grande do Sul, as chuvas ocorrem abaixo da média (Berlato & Fontana, 2003), o que contribui para a menor concentração de vapor d'água na atmosfera e resulta em menor efeito estufa e maior redução ou abaixamento da temperatura durante a noite. Quando a ODP está na fase quente, os eventos El Niño são mais intensos e frequentes (Kayano & Andreoli, 2007;Streck et al, 2009), o que contribui, no Rio Grande do Sul, para a ocorrência de chuva acima da normal do período e, consequentemente, maior teor de vapor d'água na atmosfera, que favorece a ocorrência do efeito estufa e causa menor abaixamento da temperatura noturna, como ocorreu com a máxima anual e semestral da temperatura mínima, na fase quente da ODP de 1925-1946 (Figuras 1 E, 2 E e 3 E).…”
Section: Resultsunclassified
“…The study of the series of monthly cumulated precipitation in northwestern Patagonia has confirmed the presence of negative trends in summer, even if the Mann-Kendall test did not show any statistical significance (Table 4). According to Kayano and Andreoli [4] these trends could be explained using the Pacific Decadal Oscillation (PDO). The negative trends of precipitation during the warm months will surely influence the soil water budget, increasing the soil water deficit.…”
Section: Climate Data Analysismentioning
confidence: 99%
“…Recent studies realized by Kayano and Andreoli [4] provided diagnostic evidence on modulations of El Niño-Southern Oscillation (ENSO) teleconnections by lower frequency climate modes. One of these modes is the well known Pacific (inter-)Decadal Oscillation (PDO), which explains part of the decadal-multidecadal variability in the tropical and mid latitude Pacific.…”
Section: Introductionmentioning
confidence: 99%